Abella collection a checklist with a subject index - Hernandez, Lolita P.; Picache, Ursula G.; Rata, Maria Nena (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1979)
This checklist lists books, pamphlets, unpublished materials, reprinted articles and periodicals in the Abella Collection. It consists of three chapters: Chapter I is the Introduction; Chapter II is the Biography of Dr. Domingo Abella; and Chapter III is the Bibliography proper.
The bibliography proper is arranged in two parts: Part A consists of books and pamphlets, unpublished materials and reprinted articles arranged alphabetically by author; Part B consists of periodicals arranged alphabetically by title.
A subject index to these materials is provided to facilitate the location of specific items.
Typescript.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Abella, Domingo Calleja; Abella, Domingo Calleja--Library--Bibliography.; Libraries, Private--Philippines--Bibliography.